Multivariate analysis of pesticides in environmental samples using high performance liquid chromatography - Nabi, Nusrat; Ghulam Rasool, Shahida; Nurfaizah Abu Tahrim; Sarwar, Aziza; Sherino, Bibi; Mahar, Saima; Shahid, Farkhanda (Penerbit Universiti Kebangsaan Malaysia, 2025)
In the agricultural regions of Quetta district, Pakistan, the concentrations of pesticide residues (diazinon, malathion and aldrin) were measured in vegetable, soil and water samples. A sensitive and simple method has been developed by using a chemometric approach for quantification of three pesticides, namely diazinon, aldrin, and malathion in leafy vegetables by using high-performance liquid chromatography (HPLC). In the modified ultrasonication method, the factor and responses were optimised through a central composite design. Response surface plots show the importance of sample weight and sonication time factor. This method has linearity range of 0.5 mg/kg-2.5 mg/kg, a correlation coefficient of 0.99, and a detection limit ranges between 0.01 mg/kg-3 mg/kg. The recovery ranges between 85%- 93.2%, with relative standard deviation (RSD) between 0.86%-11%. This method was applied to a real vegetable sample in the city of Quetta. Soil and water samples were also collected with these vegetable samples in different seasons. The presence of pesticides in soil and vegetable samples pose a serious risk to people who rely on these foods for sustenance. There was no significant correlation amongst the seasonal distribution of pesticides and physicochemical properties of soil indicating different application techniques and/or mechanisms rather than soil characteristics are responsible for the residue’s existence. Therefore, it is advised that continuous monitoring to be conducted in order to control the use of these insecticide in the research area.